Context aware spectrum handoff scheme in cognitive radio vehicular networks. (2017) - Kumar, Krishan; Prakash, Arun; Tripathi, Rajeev
In future cognitive radio (CR) vehicular networks deployment, multiple radio access networks may coexist in overlapping areas. These networks may have with largely different characteristics in terms of multiple attributes. Hence, it becomes difficult for CR vehicular node to select preferred network for spectrum handoff decision. This can be done by a context aware spectrum handoff that takes multiple attributes into account for spectrum handoff decision for preferred network selection. This paper proposes a context aware spectrum handoff scheme with multiple attributes decision-making (MADM) methods for preferred network selection in CR vehicular networks. The MADM methods used are simple additive weighting and grey relational analysis. The paper also proposes a cost-based spectrum handoff scheme with MADM which outperforms other MADM methods. The spectrum handoff with MADM provides wider and optimum choice with quality of service. Numerical results show that the proposed scheme is effective for spectrum handoff decision for preferred network selection.